Muscle fitness and its association with body mass index in children and adolescents aged 7-18 years in China: a cross-sectional study - Huijing He; Li Pan; Jianwei Du; Feng Liu; Yuming Jin; Jingang Ma; Li Wang; Pengben Jia; Zhiping Hu; Guangliang Shan (BMC, 2019)
Abstract Background The present study was the first one aimed to investigate the current muscle fitness and its associated factors among children and adolescents in mainland China. Methods From Nov 2013 to Jul 2014, 2283 children and adolescents aged 7-18 were recruited in Hainan and Shaanxi Provinces in China by cross-sectional design. Information on anthropometry and muscle fitness, measured by hand grip strength (GS), vertical jump (VJ) and sit-and-reach (SR), were collected. Analysis of covariance was performed by using general linear regression models to identify the association between BMI and muscle fitness. Results The means of GS, VJ and SR in boys were 22.30 ± 11.55 kg, 22.93 ± 6.80 cm and 3.58 ± 7.31 cm, respectively, and in girls were 16.61 ± 6.87 kg, 18.11 ± 4.08 cm and 7.18 ± 5.72 cm, respectively. GS (from 8.26 kg in the 7-8-year-old group to 27.91 kg in the 17-18 group) and SR (from 1.75 cm in the-8-year-old group to 10.12 cm in the 17-18 group) increased with age (both p for trend < 0.001). Boys had higher GS and VJ, but significantly lower SR than girls in each age group (p < 0.001). After adjusting for age, sex, residential areas and study regions, GS increased with elevated BMI (compared with normal weight group, the regression coefficient for thinness and overweight/obesity were − 2.997(95%CI: −3.693 to − 2.301) and 1.220 (95%CI: 0.285 to 2.155), respectively. With the p values less than 0.001 and 0.011, respectively). For VJ, there was no difference found between normal weight group and overweight/obesity group (p = 0.550), but the thinness group had the lowest performance (regression coefficient = − 2.681, 95%CI from − 3.965 to − 1.397, p < 0.001). For SR, compared with normal weight group, the regression coefficients for thinness and overweight/obesity were − 1.313(95%CI: −2.228 to − 0.399) and − 1.623(95%CI: −3.216 to − 0.030) respectively, both p < 0.05. Conclusions Increased body weight may have a positive association with isometric muscle strength measured by grip strength, but a negative one with strength of lifting the body. Sex difference was also found in the performance of flexibility.